2020
DOI: 10.1186/s12882-020-01934-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated pure red cell aplasia related with epoetin-beta pegol (C.E.R.A.) as an erythropoietic agent: case report of a dialysis patient

Abstract: Background: Erythropoietin-stimulating agents (ESAs) are used to treat anemia in patients with chronic kidney disease, enabling maintenance of stable hemoglobin levels and eliminating the need for multiple transfusions. Epoetin-beta pegol (C.E.R.A.) is a continuous erythropoietin receptor activator created by integrating a large methoxy-polyethylene-glycol-polymer chain into the erythropoietin molecule, which provides it with a longer halflife. On rare occasions, cases of antibody-mediated pure red cell aplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Epoetin-beta pegol (continuous erythropoietin receptor activator; CERA), a third-generation ESA, has also been reported in cases of confirmed antibody-mediated PRCA related to CERA. Pfizer’s Biosimilar Retacrit ® is biosimilar to Epogen® and Procrit ® (epoetin alfa) [ 11 ]. Due to exposure to different brands of ESA, which can increase the risk of PRCA, the timing of the exposure, and the route of administration, the anemia in this patient was most likely from anti-ESA antibody-mediated PRCA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epoetin-beta pegol (continuous erythropoietin receptor activator; CERA), a third-generation ESA, has also been reported in cases of confirmed antibody-mediated PRCA related to CERA. Pfizer’s Biosimilar Retacrit ® is biosimilar to Epogen® and Procrit ® (epoetin alfa) [ 11 ]. Due to exposure to different brands of ESA, which can increase the risk of PRCA, the timing of the exposure, and the route of administration, the anemia in this patient was most likely from anti-ESA antibody-mediated PRCA.…”
Section: Discussionmentioning
confidence: 99%
“…The main rationale for using immunosuppressives is to suppress antibody production [ 10 ]. A large retrospective study showed that none of the PRCA patients who did not receive immunosuppressives were considered cured, whereas 56%, 87%, 67%, and 100% were considered cured when treated with steroid, steroid plus cyclophosphamide, cyclosporine, and kidney transplantation, respectively [ 11 ]. These results suggest that immunosuppressive treatment can accelerate recovery from anti-EPO antibody-mediated PRCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Indeed, several cases of anaphylaxis and pure red cell aplasia have been reported, indicating that CERA can also promote biopharmaceutical-related immune responses. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Continuous erythropoietin receptor activator (CERA) is a third-generation ESA with a methoxy-polyethylene glycol polymer chain integrated into the erythropoietin molecule and a longer elimination half-life than previous ESAs ( 4 ). Few cases of PRCA induced by CERA and presenting with anti-epoetin beta pegol antibody have been reported ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%